Integrating Shariah-Based training methods in Malaysian Shariah Compliance 56-66 Hospitals (MSCH) - Khaliq, Zaid; Mohd. Israil, Khaliq Ahmad; Alam, Mohammad Shekaib (World Academy of Islamic Management (WAIM), 2023)
An interesting area of an emerging field of knowledge is halal management encompassing the products and services industry including training of personnel. The paper entitled, ‘Integrating Shariah-Based Training Methods in Malaysian Shariah Compliance Hospitals (MSCH)’ touches upon the seekers of halal medical services especially by Muslims. The implementation of Islamic hospital ideals in Malaysian healthcare facilities is inadequate and considered as at an infancy stage. The objective of the study is to affect a cultural shift in Shariah-compliant healthcare institutions in Malaysia through the integration of Islamic historical and cultural perspectives and metrics. This study’s scope was human talents development and is limited to examining the incorporation of Shariah principles adherence into the training methods to be utilized by these health care services providing institutions.